Additive manufacturing of continuous carbon fiber reinforced PETG with ultra-high interlaminar shear strength - Wenbo Wang; Yong Hu; Lei Yang; Yudong Lin; Lei Zhou; Jiayun Ma; Bing Liu; Xuan Cai; Chunze Yan; Yusheng Shi; Xiyong Chen (Journal of Materials Research and Technology, 2025)
Composite materials are high-performance materials formed by the optimal combination of material components with different properties through advanced material preparation techniques. In recent years, additive manufacturing of continuous fiber composites has garnered significant interest across various industries. However, additively manufactured Continuous carbon fiber reinforced composites (CCFRC) parts are still deficient in interlayer bonding strength. In this paper, modified equipment based on commercial Fused Deposition Modeling (FDM) has been developed for the additive manufacturing of CCFRC. The equipment was improved to address the problems of too sharp nozzle, insufficient traction force of continuous fiber, insufficient level of hot bed, and humidity of filament. To improve the CCFRC interlayer bonding strength, this paper explores the effects of different hatch spacing and printing speeds on the interlayer shear strength of the specimens. The results show that smaller hatch spacing can print components with higher Interlaminar Shear Strength (ILSS), while either too large or too small a printing speed will result in greater porosity and thus a decrease in the ILSS of the part. After the optimization, the maximum interlaminar shear strength and the maximum relative density of the produced samples reach 27.41 MPa and 99.47% with the parameters of hatch spacing 0.8 mm and printing speed 2 mm/s. Finally, the mechanism analysis of the above improvement and parameter optimization is carried out by relative density and surface morphology. It can provide guidance for interlaminar reinforcement of CCFRC parts for additive manufacturing.